2010
DOI: 10.1590/s0006-87052010000200009
|View full text |Cite
|
Sign up to set email alerts
|

Controle de plantas daninhas na cultura de soja resistente ao glyphosate

Abstract: RESUMOO objetivo da pesquisa foi avaliar o controle de plantas daninhas em área cultivada com soja resistente ao herbicida glyphosate, sem a utilização de práticas complementares de manejo de plantas daninhas. Foram desenvolvidos experimentos, em condições de campo, nos anos agrícolas 2005 e 2006/2007. Foram avaliadas duas cultivares de soja resistentes ao glyphosate (CD 214 RR e M-SOY 8008 RR), oito tratamentos de herbicidas (glyphosate, em aplicação única, nas doses de 0,48; 0,72; 0,96 e 1,20 kg ha -1 de equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…Gnaphalium coarctatum acted as typical of Group 3 (6001 to 8000 g ha -1 -average use standard) and the specie Urochloa decumbens was representative for Group 4 (8001 to 10000 g ha -1 -high use standard). According to Correia and Duringan (2010), the weed control is directly influenced by the rates of glyphosate. Some species may require higher doses of glyphosate, or sequential applications, addition of another herbicide for more effective control (Ateh and Harvey, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Gnaphalium coarctatum acted as typical of Group 3 (6001 to 8000 g ha -1 -average use standard) and the specie Urochloa decumbens was representative for Group 4 (8001 to 10000 g ha -1 -high use standard). According to Correia and Duringan (2010), the weed control is directly influenced by the rates of glyphosate. Some species may require higher doses of glyphosate, or sequential applications, addition of another herbicide for more effective control (Ateh and Harvey, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Correia and Durigan (2010) found that weed control in cultivation of soybean RR is directly influenced by the dose of this herbicide, with satisfactory control with a single application of 960 g ha depending on the weed species. In this context, it is noteworthy that the sequential application of glyphosate in soybean RR, practice commonly adopted by the producers, represent alternative for the control ** and *: significant at 1 and 5% probability, respectively.…”
Section: Experiments 2 -Control Of Castor Bean Volunteer Plant In Postmentioning
confidence: 99%
“…With the development of genetically modified soybean cultivars resistant to glyphosate, weed management somehow has lost its importance. However, the continuous use of glyphosate may, over time, lead to the emergence of resistant biotypes (Correia & Durigan, 2010 (EMBRAPA, 2013).…”
Section: Amongmentioning
confidence: 99%